Associations of disaster-related and psychosocial factors with changes in smoking status after a disaster: a cross-sectional survey after the Great East Japan Earthquake. Issue 6 (30th June 2018) - Nakano, Hironori; Ohira, Tetsuya; Maeda, Masaharu; Yabe, Hirooki; Ohtsuru, Akira; Suzuki, Yuriko; Harigane, Mayumi; Horikoshi, Naoko; Nagai, Masato; Zhang, Wen; Takahashi, Hideto; Yasumura, Seiji; et al.
Abstract : Objective: Few studies have comprehensively examined changes in smoking status and related factors after a disaster. We examined these factors among residents of an evacuation area in Fukushima after the Great East Japan Earthquake. Methods: The study participants included 58 755 men and women aged ≥20 years who participated in the Fukushima Health Management Survey in 2012 after the disaster. Smoking status was classified as either current smokers or current non-smokers before and after the disaster. The participants were divided into the following groups: (1) non-smokers both before and after the disaster, (2) non-smokers before and smokers after the disaster, (3) smokers before and non-smokers after the disaster and (4) smokers both before and after the disaster. The adjusted prevalence ratios and 95% CIs of changes in smoking status for demographic, disaster-related and psychosocial factors were tested using logistic regression analysis that was stratified by smoking status before the disaster. Results: Among the 44 729 participants, who were non-smokers before the disaster, 634 (1.4%) began smoking after the disaster. Among the 14 025 smokers before the disaster, 1564 (11.1%) quit smoking after the disaster, and the proportion of smokers in the evacuation area consequently decreased from 21.2% to 19.6%. In the multivariable model, factors significantly associated with beginning smoking included being a male, being younger, having a lower education, staying in a rental house/apartment, house being damaged, having experienced a tsunami, change jobs and the presence of traumatic symptoms and non-specific psychological distress. On the contrary, factors associated with quitting smoking included being a female, being older, having a higher education and having a stable income. Conclusion: The proportion of smokers slightly decreased among residents in the evacuation area. The changes in smoking statuses were associated with disaster-associated psychosocial factors, particularly changes in living conditions, having experienced a tsunami, change jobs and developing post-traumatic stress disorder.